Efficacy and safety of immune checkpoint inhibitors-combined antiangiogenic drugs in the treatment of hepatocellular carcinoma: A systematic review and meta analysis - Zhong, Yu; Huo, Hong; Dai, Shuqi; Li, Su (Frontiers in Oncology, 2022)
Background: Hepatocellular carcinoma is a pathological type of liver cancer and accounts for the majority of primary liver cancers. We conducted a meta-analysis to evaluate the efficacy and safety of immune checkpoint inhibitors in combination with antiangiogenic drugs in the treatment of hepatocellular carcinoma. Methods: We searched scientific literature databases and clinical trials databases through May 2022 for required studies. Progression-free survival was taken as the main outcome, and overall survival, response rate and adverse events as secondary outcomes. These data were extracted, combined and used for meta-analysis to compare the treatment effect and safety of immune checkpoint inhibitors combined with antiangiogenic drugs in patients with advanced/unresectable/metastatic hepatocellular carcinoma. Results: This study included 3 randomized controlled trials and 6 single-arm trials of immune checkpoint inhibitors in combination with antiangiogenic drugs in hepatocellular carcinoma. Meta-analysis showed that compared with single use, combination of the two can significantly improve PFS (HR=5.93, 95% CI=5.41, 6.45) and OS (HR=15.84, 95% CI=15.39, 16.28). The ORR and DOR of patients with combination therapy were HR=19.11, 95% CI=15.99, 22.22 and HR=12.26, 95% CI=10.32, 14.21, respectively. Common adverse reactions to combination therapy included hypertension (26.8%), diarrhea (23.6%), fatigue (23.8%), decreased appetite (22.8%), hypothyroidism (9.9%), and rash (14.5%). Conclusion: In the treatment of advanced/unresectable/metastatic hepatocellular carcinoma, immune checkpoint inhibitors combined with antiangiogenic drugs achieved better survival benefits than alone. In addition, the combination therapy has tolerable safety.